Analisis Kandungan Metabolit Sekunder, Antioksidan dan Uji Aktivitas Antibakteri Minuman Tradisional Serbat Khas Kalimantan Barat dengan Variasi Komposisi dan Lama Perendaman - Syarifah NYRS Asseggaf; Mistika Zakiah; Ridha Ulfah (Jurnal Kesehatan Andalas, 2022)
Serbat drink is a traditional drink typical of the Malay of West Kalimantan made from plant spices usually served in the Saprahan tradition. Serbat drinks are widely circulated among the public because, empirically, they are useful for health problems, one of which is to treat diarrhea. Objectives: To analyzed the content of secondary metabolites, antioxidant activity, and antibacterial activity of serbat drink on the growth of Escherichia coli bacteria which were known from the presence or absence and measurement of the length of the inhibition zone (the clear area around the disc) with the positive control, namely ciprofloxacin, and negative control, namely distilled water. Methods: The plant spices used in this research include cardamom, cloves, star anise, cinnamon, pandan leaves, sappan wood, anise, and ginger. Serbat drink was made in 3 variations, namely composition A, composition B, and composition C. The three composition variations were carried out for two soaking times, namely 15 minutes and 540 minutes. This study used the thin-layer chromatography (TLC) method for phytochemical screening, the DPPH (2,2-diphenyl-1-pikrilhidrazil) method for examination of antioxidant activity, and Escherichia coli bacteria cultured in 3 agar and tested using the disc diffusion method (Kirby-Bauer) to determine its antibacterial activity.  Results: The secondary metabolites contained in each serbat water sample, antioxidant activity from strongest to weakest among the serbat samples, and the absence of visible inhibition zones. Conclusion: Serbat drink does not have antibacterial activity against Escherichia coli.Keywords:  secondary metabolites, serbat drink, variations in composition, variations in the soaking time